Identification of a novel HLA‐B*15 variant allele, HLA‐B*15:276, in an umbilical cord blood donor. Issue 6 (20th March 2014) - Barbuti, S.; Sciarrino, R.; Mariotti, M.; Curcio, M.; Scatena, F.
<x xml:space="preserve">Abstract</x> A newly identified allele, named HLA B*15:276, differs from B*15:01:01:01 by the single nucleotide substitution 511T‐C at codon 147 (Trp → Arg) in exon 3.